Bacterial aerobic synthesis of nanocrystalline magnetite - Bharde, Atul A.; Wani, A.; Shouche, Y.; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Journal of the American Chemical Society, 2005)

Biological synthesis of stable vaterite crystals by the reaction of calcium ions with germinating chickpea seeds - Rautaray, D.; Sanyal, A.; Bharde, Atul A.; Ahmad, Absar; Sastry, M. (Crystal Growth & Design, 2005)
The total biological synthesis of CaCO3 crystals of the metastable vaterite polymorph at room temperature by simple protein-mediated reaction of aqueous Ca2+ ions with the CO2 generated during the root growth from germinating chickpea (Cicer arietinum) seeds is described. Highly stable vaterite crystals of spherical morphology are obtained, indicating that the proteins secreted from the roots during growth play a crucial role in stabilizing and directing the crystal growth.

Biosynthesis of gold and silver nanoparticles using emblica officinalis fruit extract, their phase transfer and transmetallation in an organic solution - Ankamwar, Balaprasad; Damle, C.; Ahmad, Absar; Sastry, M. (Journal of Nanoscience and Nanotechnology, 2005)
The design, synthesis and characterization of biologically synthesized nanomaterials have become an area of significant interest. In this paper, we report the extracellular synthesis of gold and silver nanoparticles using Emblica Officinalis (amla, Indian Gooseberry) fruit extract as the reducing agent to synthesize Ag and Au nanoparticles, their subsequent phase transfer to an organic solution and the transmetallation reaction of hydrophobized silver nanoparticles with hydrophobized chloroaurate ions. On treating aqueous silver sulfate and chloroauric acid solutions with Emblica Officinalis fruit extract, rapid reduction of the silver and chloroaurate ions is observed leading to the formation of highly stable silver and gold nanoparticles in solution. Transmission Electron Microscopy analysis of the silver and gold nanoparticles indicated that they ranged in size from 10 to 20 nm and 15 to 25 nm respectively. Ag and Au nanoparticles thus synthesized were then phase transferred into an organic solution using a cationic surfactant octadecylamine. Transmetallation reaction between hydrophobized silver nanoparticles and hydrophobized chloroaurate ions in chloroform resulted in the formation of gold nanoparticles.
Keywords: Biosynthesis; Nanomaterials; Phase transfer; Transmetallation

Calcite growth in Cissus quadrangularis plant extract, a traditional Indian bone-healing aid - Sanyal, A.; Ahmad, Absar; Sastry, M. (Current Science, 2005)
Cissus quadrangularis, a plant that has been customarily used in the Indian subcontinent to hasten the process of healing in bone fractures, has been studied and exploited to synthesize calcite crystals. The plant extract serves as a rich source of calcium ions, which when reacted with CO2, leads to the formation of calcite crystals of highly irregular morphology indicating that bioorganic molecules present in the extract modulate the crystal morphology.
Keywords: bone fracture; calcite crystals; Cissus quadrangularis; traditional healing

Cobalt and magnesium ferrite nanoparticles: preparation using liquid foams as templates and their magnetic characteristics - Bala, Tanushree; Sankar, C. R.; Baidakova, Marina; Osipov, V.; Enoki, Toshiaki; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Langmuir, 2005)
An easy and convenient method for the synthesis of cobalt and magnesium ferrite nanoparticles is demonstrated using liquid foams as templates. The foam is formed from an aqueous mixture of an anionic surfactant and the desired metal ions, where the metal ions are electrostatically entrapped by the surfactant at the thin borders between the foam bubbles and their junctions. The hydrolysis is carried out using alkali resulting in the formation of desired nanoparticles, with the foam playing the role of a template. However, in the formation of ferrites with the formula MFe2O4, where the metal ion and iron possess oxidation states of +2 and +3, respectively, forming a foam from a 1:2 mixture of the desired ionic solutions would lead to a foam composition at variance with the original solution mixture because of greater electrostatic binding of ions possessing a greater charge with the surfactant. In our procedure, we circumvent this problem by preparing the foam from a 1:2 mixture of M2+ and Fe2+ ions and then utilizing the in situ conversion of Fe2+ to Fe3+ under basic conditions inside the foam matrix to get the desired composition of the metal ions with the required oxidation states. The fact that we could prepare both CoFe2O4 and MgFe2O4 particles shows the vast scope of this method for making even multicomponent oxides. The magnetic nanoparticles thus obtained exhibit a good crystalline nature and are characterized by superparamagnetic properties. The magnetic features observed for CoFe2O4 and MgFe2O4 nanoparticles are well in accordance with the expected behaviors, with CoFe2O4 particles showing higher blocking temperatures and larger coercivities. These features can easily be explained by the contribution of Co2+ sites to the magnetocrystalline anisotropy and the absence of the same from the Mg2+ ions.

Controlling the optical properties of lemongrass extract synthesized gold nanotriangles and potential application in infrared-absorbing optical coatings - Shankar, S. S.; Rai, A.; Ahmad, Absar; Sastry, M. (Chemistry of Materials, 2005)
Anisotropic metal nanoparticles have distinct optical behavior when compared with their spherical counterparts. In this report, we demonstrate a simple method involving the reduction of aqueous gold ions by the extract of the lemongrass plant leading to the formation of gold nanotriangles with interesting absorption in the near-infrared (NIR) region of the electromagnetic spectrum. We show that, by simple variation of the experimental conditions, it is possible to vary the size of the gold nanotriangles and, thus, to tune the absorbance of flat gold nanoparticles in the NIR region. The NIR absorption of the gold nanotriangles is expected to be of application in hyperthermia of cancer cells and in IR-absorbing optical coatings. We show that the lemongrass extract synthesized gold nanotriangles can be easily cast in the form of films on glass substrates and that these films are highly efficient in absorbing IR radiation for potential architectural applications.

Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

Formation of BaCrO4 nano crystallites within thermally evaporated sodium bis-2-ethylhexyl-sulfosuccinate and stearic acid thin films - Rautaray, D.; Sinha, K.; Sainkar, S. R.; Pasricha, R.; Pavaskar, N. R.; Sastry, M. (Journal of the American Ceramic Society, 2005)
This paper describes the growth of barium chromate (BaCrO4) nanocrystallites within thermally evaporated thin films of stearic acid (StA) and sodium bis-2-ethylhexyl-sulfosuccinate by a process of Ba2+ ion entrapment followed by in situ reaction CrO42- ions. Dense spherical assemblies of BaCrO4 nanocrystallites of very uniform size (similar to50 nm) were obtained within the two different host matrices. The spherical assemblies were composed of smaller (ca. 5-10 nm size) BaCrO4 crystals indicating that efficient size control over crystal size may be exercised by the matrix. Contact angle measurements of the BaCrO4-StA and BaCrO4-sodium bis-2-ethylhexyl-sulfosuccinate films indicated that they were hydrophobic, thus pointing to the possible role of hydrophobic interaction between the StA and sodium bis-2-ethylhexyl-sulfosuccinate monolayer-covered BaCrO4 crystals in the assembly process.

Gold nanoparticle networks with photoresponsive interparticle spacings - Sidhaye, D. S.; Kashyap, Sudhir; Sastry, M.; Hotha, Srinivas; Bhagavatula L. V. Prasad (Langmuir, 2005)
Photoresponsive gold nanoparticle networks were prepared by functionalizing them with azobenzene derivatives. A network can be formed when a linker molecule constituting the azobenzene moiety suitably derivatized on either side with gold surface sensitive groups such as thiols and amines is added to the nanoparticle solution. It is shown that the interparticle spacing in the networks could be controlled by the reversible trans-cis isomerization of the azobenzene moiety induced by UV and visible light, respectively. The photoinduced variation in the interparticle spacings is inferred by the changes in the optical spectra of the gold nanoparticles which display a red or blue shift in the surface plasmon resonance peak depending on a decrease or increase in the interparticle spacing, respectively. Transmission electron microscopy images are in consonance with the evidence from the optical spectra.

Interfacing biology with nanoparticles - Mandal, Sujata; Phadtare, S.; Sastry, M. (Current Applied Physics, 2005)
New approaches are constantly being developed for both the synthesis of inorganic nanomaterials and their surface modification for sensing and electronic applications. Insofar as surface modification of gold nanoparticles is concerned, thiol chemistry is the most popular approach to bind ligands to their surface. We have been pursuing the possibility of using amine functionality to bind ligands to the surface of gold nanoparticles and have found that amine binding is as strong as thiol binding. The advantages of using amine chemistry for surface modification of nanogold are many, the possibility of complexing a large variety of biomolecules such as amino acids and proteins being one of the most important. In this article, we review the work from this laboratory on the stabilization of gold nanoparticles using amino acids as well as using amino acids as reducing agents to obtain stable aqueous solutions of gold nanoparticles of variable size. We also discuss the possibility of forming bioconjugates of enzymes with gold nanoparticles decorating the surface of polymer microspheres and their application as reusable biocatalysts. There is much to be gained by marrying nanomaterials with biology with considerable spin-offs likely in both nanotechnology and biotechnology. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: amino acids' enzyme immobilization; Nanoparticles; Proteins

Keggin ion mediated synthesis of hydrophobized pd nanoparticles for multifunctional catalysis - Mandal, Sujata; Das, Amitava; Srivastava, R.; Sastry, M. (Langmuir, 2005)
Development of simple and reliable protocols for the synthesis of organically soluble catalytically active metal nanoparticles is an important aspect of research in nanomaterials. We demonstrate herein the formation of Pd nanoparticles by reduction of aqueous Pd(NO3)(2) by photoexcited Keggin ions (phosphotungstate anions). This results in the formation of Pd nanoparticles capped with with Keggin ions that render the particles negatively charged. The Keggin ion capped Pd nanoparticles may then be phase transferred into nonpolar organic solvents such as toluene by electrostatic complexation with cationic surfactants such as octadecylamine at the liquid-liquid interface. This results in a new class of catalyst wherein both the Pd core and Keggin ion shell may be used in a range of catalytic reactions leading to a truly multifunctional catalyst dispersible in organic solvents.

New approaches to the synthesis of anisotropic, core-shell and hollow metal nanostructures - Sastry, M.; Swami, A.; Mandal, Sujata; Selvakannan, P. R. (Journal of Materials Chemistry, 2005)
The synthesis of nanomaterials with control over size, shape and chemical composition continues to be a major challenge in nanoscience. The requirements of nanomaterial synthesis are becoming more sophisticated and, in addition to anisotropic structures, there is much excitement surrounding the development of recipes for the synthesis of core-shell and hollow nanostructures. Much of the motivation for research in this direction stems from the unusual optoelectronic and chemical properties exhibited by such nanostructures. In this article, we review the work from this laboratory on the synthesis of flat gold nanostructures at the air-water interface, either by confining the reductant or the precursor metal ions to the air-water interface. We also describe the synthesis of phase-pure core-shell nanoparticles by immobilizing UV- and pH-dependent reducing agents on the surface of the core nanoparticles as well as the synthesis of organically soluble hollow-shell nanostructures via transmetallation reactions.

Phase transfer of oleic acid capped NicoreAgshell nanoparticles assisted by the flexibility of oleic acid on the surface of silver - Bala, Tanushree; Swami, A.; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Colloid and Interface Science, 2005)
The phase transfer protocols in vogue for the oleic acid capped silver nanoparticles, viz., salt-induced precipitation and redispersion or phosphoric acid-induced method, are examined and compared thoroughly. A comprehensive evaluation with respect to the mechanistic aspects involved is made and the merits and demerits of the different procedures are delineated. It is found that the salt-induced precipitation and redispersion is more versatile in that the precipitate can actually be redispersed in both aqueous and organic media. However, in terms of mechanism both the routes seem to be very similar wherein the orientational change of oleic acid on the silver surface in the two different environments-organic and aqueous-plays a crucial role in the adaptability of the system to the different environments. Subsequently, this change of orientation of oleic acid on silver surface in aqueous and organic media has been utilized to phase transfer Ni-based nanoparticulate systems. The nascent oleic acid-capped Ni nanoparticles, which were synthesized by a foam-based protocol, were dispersible in water but not in nonpolar organic media such as cyclohexane or toluene. Then, just by coating a thin shell of silver on them we could achieve complete phase transfer of the NicoreAgshell from aqueous to organic media following similar procedures used for oleic acid-capped silver nanoparticles. Here, the phase transfer seems to be facilitated by the orientational flexibility of oleic acid on the silver surface as opposed to other metal surfaces as evidenced from the infrared and thermogravimetric analyses of oleic acid-capped Ni and NicoreAgshell nanoparticles. This orientation-assisted phase transfer method could be generalized and can be adapted to other systems where, if the nascent nanoparticles cannot be phase transferred as is, they can be coated by a silver shell and oleic acid making them suitable for dispersion in both aqueous and organic media. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: (1) HNMR; FTIR; Phase transfer; transmetalation core-shell nanoparticles; UV-Vis

Role of Mg ions in modulating the morphology and structure of CaCO3 crystals grown in aqueous foams - Rautaray, Debabrata; Kasture, Manasi; Sastry, M. (CrystEngComm, 2005)
We investigate the role of magnesium ions in modulating the morphology and crystallography of CaCO3 crystals grown in aqueous foam. This is accomplished by first making foams from an aqueous mixture of CaCl2+MgCl2 and the anionic surfactant aerosol-OT (AOT) followed by reaction of the foam with Na2CO3 solution. The Ca2+ and Mg2+ ions electrostatically complex with AOT and react with Na2CO3 within the foam to yield CaCO3 crystals of interesting morphology. These studies indicate that CaCO3 in a fractured, needle-like morphology was formed at high Mg2+ concentrations in the foam whereas porous, rhombic CaCO3 crystals were obtained at low Mg2+ concentrations. The effect of water drainage time and thereby, the structure of the foam on the morphology of the CaCO3 crystals grown was also studied.

Silver nanoparticles of variable morphology synthesized in aqueous foams as novel templates - Mandal, Sujata; Arumugam, S. K.; Pasricha, R.; Sastry, M. (Bulletin of Materials Science, 2005)
In this paper, we describe the synthesis of silver nanocrystals within aqueous foams as a template More specifically, we show that aqueous Ag+ ions may be electrostatically complexed with the anionic surfactants aerosol OT (sodium bis-2-ethylhexyl-sulfosuccinate, (AOT) and sodium dodecyl sulphate (SDS)) in a highly stable liquid foam. After drainage of the foam, the silver ions are reduced in situ by introducing sodium borohydride into the foam by capillary flow. This leads to the formation of silver nanoparticles of spherical, tape- and sheet-like morphology in the foam. The structure of the foam is extremely complex and presents reaction sites of different spatial extent. The differences in foam reaction-site geometry are believed to be responsible for the morphology variation in the silver nanoparticles observed. The silver nanoparticles are observed to be extremely stable in solution suggesting that the AOT or SDS molecules stabilize them. This approach appears promising for application in large-scale synthesis of nanoparticles and may be readily extended to other chemical compositions.
Keywords: Chemical synthesis; composites; foam; Intercalation; Nanoparticles

Solvent-adaptable silver nanoparticles - Bhagavatula L. V. Prasad; Arumugam, S. K.; Bala, Tanushree; Sastry, M. (Langmuir, 2005)
A simple and efficient way of obtaining silver nanoparticles that are dispersible both in organic and in aqueous solvents using a single capping agent is described. The silver nanoparticles are initially prepared in water in the presence of aerosol OT [sodium bis(2-ethylhexyl)-sulfosuccinate, AOT]. Thereafter, transfer of the AOT-capped silver nanoparticles to an organic phase is induced by the addition of a small amount of orthophosphoric acid during shaking of the biphasic mixture. The AOT-stabilized silver nanoparticles could be separated out from the organic phase in the form of a powder. The hydrophobic nanoparticles thus prepared are stable and are readily resuspended in a variety of other polar (including water) and nonpolar solvents without further surface treatment. The amphiphatic nature of the silver surface is brought about by a small orientational change in the AOT monolayer on the silver surface in response to the polarity of the solvent.

Synthesis and assembly of gold nanoparticles in quasi-linear lysine-keggin-ion colloidal particles - Sanyal, A.; Mandal, Sujata; Sastry, M. (Advanced Functional Materials, 2005)
The formation of fiber-like colloidal particles of the amino acid lysine complexed with Keggin ions is demonstrated. The lysine-phosphotungstic acid (PTA) colloidal particles act as excellent templates for the synthesis and assembly of gold nanoparticles wherein the lysine-PTA complex acts as a UV-switchable reducing agent for gold ions. This novel bio-organic-inorganic template shows excellent potential as a regulated nanoreactor for application in programmed nanoparticle synthesis and assembly in a single step.

Synthesis of gold, silver and their alloy nanoparticles using bovine serum albumin as foaming and stabilizing agent - Singh, A. V.; Bandgar, B. M.; Kasture, Manasi; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Materials Chemistry, 2005)
A simple and convenient method for the synthesis of gold, silver and their alloy nanoparticles in a foam matrix using the protein bovine serum albumin (BSA) is reported. BSA is an excellent foaming agent and, by virtue of its zwitterionic character at the protein isoelectric point, may be used to bind to either cationic silver (Ag+) or anionic gold (AuCl4-) ions in the foam. The metal ions in the foam are thereafter reduced in situ to yield silver and gold nanoparticles. The versatility of an amphoteric foaming agent is further demonstrated by the simultaneous binding of Ag+ and AuCl4- ions with zwitterionic BSA leading to the possibility of obtaining Au-Ag alloy nanoparticles in the foam. The BSA molecules coat and stabilize the nanoparticles thus prepared eliminating the necessity of employing an additional stabilizing agent in the experimental recipe.

Synthesis of hydroxyapatite crystals using amino acid-capped gold nanoparticles as a scaffold - Rautaray, D.; Mandal, Sujata; Sastry, M. (Langmuir, 2005)
Inorganic composites are of special interest for biomedical applications such as in dental and bone implants wherein the ability to modulate the morphology and size of the inorganic crystals is important. One interesting possibility to control the size of inorganic crystals is to grow them on nanoparticles. We report here the use of surface-modified gold nanoparticles as templates for the growth of hydroxyapatite crystals. Crystal growth is promoted by a monolayer of aspartic acid bound to the surface of the gold nanoparticles; the carboxylate ions in aspartic acid are excellent hinging sites for Ca2+ ions. Isothermal titration calorimetry studies of Ca2+ ion binding with aspartic acid-capped gold nanoparticles indicates that the process is entropically driven and that screening of the negative charge by the metal ions leads to their aggregation. The aggregates of gold nanopartictes are believed to be responsible for assembly of the platelike hydroxyapatite crystals into quasi-spherical superstructures. Control experiments using uncapped gold nanoparticles and pure aspartic acid indicate that the amino acid bound to the nanogold surface plays a key role in inducing and directing hydroxyapatite crystal growth.

La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Role of halide ions and temperature on the morphology of biologically synthesized gold nanotriangles - Rai, A.; Singh, A.; Ahmad, Absar; Sastry, M. (Langmuir, 2006)
{In this paper, we demonstrate the effect of halide ions on the formation of biogenically prepared gold nanotriangles using the leaf extract of lemongrass (Cymbopogonflextiosus) plant. We have also studied the effect of halide ions on the morphology of biogenic nanotriangles. It has been shown that iodide ions have a greater propensity to transform flat gold nanotriangles into circular disklike structures as compared to other halide ions. The study also suggests that the presence of Cl- ions during the synthesis promotes the growth of nanotriangles, whereas the presence of I- ions distorts the nanotriangle morphology and induces the formation of aggregated spherical nanoparticles. The change in the morphology of gold nanotriangles has been explained in terms of the ability of the halide ions to stabilize or inhibit the formation of (I 11) faces to form [
Keywords: DME steam reforming; fuel cells; Hydrogen; Mixed oxides; supported Ga2O3; XPS